REDEFINING SCHOOL COEXISTENCE PROCESSES WITH POSITIVE DISCIPLINE - Yojana Mena Cuesta; Yency Marina Valencia Mena; Yarley Osir Díaz Hinestroza (DIALÉCTICA, 2026)
In the field of education, it is imperative to preserve environments that promote the holistic development of students. The purpose of this essay is to analyze, from two perspectives, the contribution of positive discipline to the processes of coexistence in primary education and to identify strategies that redefine interaction in the classroom. This reflection is based on a critical-reflective analysis of documents, through which pedagogical theories and experiences were compared. The findings of the analysis show that positive discipline catalyzes significant transformations in school dynamics by focusing on mutual respect, self-regulation, and emotional connection. The implementation of participatory agreements, dialogue circles, and teacher modelling, among other things, leads to profound changes in institutional culture. It is concluded that this methodology is an essential tool for regulating disruptive behaviour, overcoming punitive models to consolidate harmonious and transformative coexistence.